Acute pancreatitis caused by pemetrexed, carboplatin, and gemcitabine in a patient with lung cancer: A rare case report - Vishal Kulkarni; B J Srinivasa; P K Kiran; Vinu Sarathy; S Shivakumar Swamy; Radheshyam Naik (Indian Journal of Medical and Paediatric Oncology)
Drug-induced pancreatitis is reported as one of the less common causes of acute pancreatitis. Many drugs such as sulfonamides, estrogens, tetracyclines, valproic acid, antiretroviral drugs, some chemotherapy drugs such as azathioprine, and 6 MP are known to cause acute pancreatitis. We report a case of acute pancreatitis following administration of chemotherapy for non-small cell lung cancer (NSCLC). The patient was diagnosed to have NSCLC (histologically proven adenocarcinoma). After thorough evaluation including radiological investigations consisting of a positron-emission tomography computed tomography scan, he was staged as a Stage III B NSCLC. As per protocol, he was started on combination chemotherapy with pemetrexed and carboplatin. After 2 weeks of chemotherapy, he developed acute pancreatitis which was managed conservatively. He was administered different drug combination during the next cycle involving gemcitabine and carboplatin. However, he developed recurrent acute pancreatitis which was managed conservatively. He was then referred to the radiotherapy department as it was deemed that he is at risk of recurrent episodes of pancreatitis if further cycles of chemotherapy are continued.